Der Grundstein : . Der Grundstein : Zeitschrift der Industriegewerkschaft Bau-Steine-Erden
Till (2000): Der Grundstein : Zeitschrift der Industriegewerkschaft Bau-Steine-Erden. Till (2000): IG Bau-Steine-Erden (BRD).